Epidemiology of chronic inflammatory demyelinating polyneuropathy in the South-Eastern area of Santiago, Chile. (April 2020) - Cea, Gabriel; Idiáquez, Juan Francisco; Salinas, Rodrigo; Matamala, José Manuel; Villagra, Roque; Stuardo, Andrés
Highlights: This is the first epidemiological study of CIDP in South America and the Caribbean. Epidemiology of CIDP in Chile is similar to other regions of the world. Frequency of CIDP in Chile is marginally greater in men than in women. Abstract: Chronic inflammatory demyelinating polyneuropathy (CIDP) is an immune-mediated polyneuropathy. It usually has an insidious onset, progressive course and heterogeneous clinical features. As far as we know, there is no epidemiological information on CIDP in South America and the Caribbean. Our aim was to estimate the frequency of CIDP in the South-Eastern region of Santiago, where our hospital is based and the population number assigned is officially reported every year by the health authorities. Records of 581 patients registered with the diagnosis of neuropathy were found and all patients meeting the diagnostic criteria of the EFNS/PNS for definitive and possible CIDP were included. Data were collected using a data extraction protocol designed by the authors and which included demographic, clinical, laboratory and electrophysiological information. The estimated prevalence and incidence of CIDP were 2.95/100, 000 and 0.46/100, 000 respectively. Fifteen patients (8 men, 7 women) were classified as definitive or possible CIDP. Nine patients had typical CIDP and three also had diabetes mellitus. The prevalence and incidence rates were similar to those reported in other regions of the world.